The Influence of Service Quality on Ladyflame Customers Satisfaction In Bandar Lampung - Saputra, Deni Eka; Karsinah, Karsinah; Jaya, Indra (Proceeding International Conference on Information Technology and Business, 2023)
This research aims to determine the impact of service quality on customer satisfaction at Ladyflame, Bandar Lampung. The problem studied in this study is whether there is a positive relationship between the quality of service and customer satisfaction of Ladyflame in Bandar Lampung. This research uses survey methods and questionnaires as data collection instruments. With 33 respondents involved. The variables studied covered the quality of service, customer satisfaction, and the relationship between the two. The results of the research show that the quality of service has a significant impact on customer satisfaction of Ladyflame. Factors such as hospitality staff, product availability, service speed, and product quality play an important role in increasing customer satisfaction. The findings provide valuable insights for Ladyflame management in Bandar Lampung to improve the quality of their services, with the aim of increasing customer satisfaction. With a deep understanding of the role of service quality in retaining and attracting customers, ladyflame can take more effective steps to meet customer expectations and maintain their market share.Â Keywords : Quality of service, customer satisfaction